IMMU-36. IMMUNE RESPONSES IN CANINE GLIOMAS ARE ENRICHED AT THE INFILTRATING EDGE OF ASTROCYTOMAS. (5th November 2018) - Kassab, Cynthia; Levine, Jonathan; Boudreau, Beth; Ling, Xiaoyang; Burks, Jared K; Zhou, Shouhao; Verhaak, Roel; Heimberger, Amy
Abstract: BACKGROUND: Immune competent spontaneously-arising gliomas in canines could be used to robustly vet immune therapeutic strategies, yet the immune composition in these CNS tumors has not been well characterized. Furthermore, few studies have examined the differences in immune reactivity between different areas of the tumor microenvironment such as the hypoxic core or the infiltrating edge. METHODS: Immunohistochemistry was used to analyze the distribution of CD3+, CD4+, and CD49a (tissue-resident memory) T cells, CD14+ monocytes, and IBA-1+ macrophages/microglia (incorporating their skew to M2 macrophages based on CD163 expression) in various tumor compartments including at the invasive edge and within the tumor or necrotic center. Tissue segmentation of canine oligodendrogliomas (n=4) and astrocytomas (n=7) was performed at 20x (0.75 NA) magnification using Perkin Elmer Vectra 3 and InForm software (Ver 2.2). Bayesian multilevel logistic regression was used to assess the immune reactivity in the various tumor compartments. RESULTS: Among the various immune populations, canine gliomas were most populated with macrophages, which constituted between 20%-30% of the total cellular population—similar to human gliomas. The macrophages were enriched at the invasive edge (OR, 1.63; 95% CI, 1.61 to 1.65). Monocytes were the next most frequent immune cell population followed by CD3, CD4, and CD49a, with all the T-cell types being rare in all tumor compartments. CD3 (OR, 1.86; 95% CI, 1.01 to 3.87), CD4 (OR, 6.2; 95% CI, 1.22 to 200), and CD163 (OR, 2.75; 95% CI, 1.12 to 37.17) at the invasive edge and CD49a (OR, 1.99; 95% CI, 1.09 to 5.19) within the tumor were more common in astrocytomas than oligodendrogliomas. The necrotic core was almost exclusively infiltrated with macrophages and monocytes. CONCLUSION: Astrocytic tumors are more immunogenic than oligodendrogliomas in canine models and are highly enriched with macrophages that predominate at the infiltrating edge.